P18 Appropriateness of antibiotic prescriptions for children and adolescents attending emergency departments for pharyngotonsillitis. Issue 6 (17th May 2019) - Messina, F; Clavenna, A; Cartabia, M; Bortolotti, A; Fortino, I; Merlino, L; Bonati, M
Abstract : Background: Qualitative and quantitative differences in the antibiotic prescription profiles for paediatric outpatients have been found between and within countries, and Italy has a high prevalence of prescriptions and frequent use of cephalosporins and macrolides. Scant data, on small samples, are available concerning the prescription profiles in emergency departments (ED), also in Italy. Methods: The data sources were administrative healthcare databases of the Lombardy region (16% of the national paediatric population). Children and adolescents between 1 and 13 years old with an ED access and an antibiotic prescription in the first semester of 2012 represented the target population. Subjects with ED access, hospital admissions, or antibiotic prescriptions in the previous two months were excluded, and the analyses were focused on children visited for pharyngotonsillitis. The percentage of subjects receiving amoxicillin (first-choice antibiotic) and the percentages receiving macrolides or cephalosporins (second-choice therapies) were estimated. Results: During the observation period 23, 216 children attended the ED for upper respiratory tract infections, 9, 611 of which were visited for pharyngotonsillitis. In all, 5, 427 (56%) children with pharyngotonsillitis received an antibiotic prescription: 24% were given amoxicillin and 18% received macrolides or cephalosporins. The percentage of children treated with amoxicillin decreased with increasing age (from 31% in 1–2 year olds to 15% in 10–13 year olds). On the contrary, the prescription of second choice treatments increased with age, reaching 23% in children 10–13 years old. Only in 5 out of 56 EDs more than half of children with pharyngotonsillitis received amoxicillin, while in 5 other EDs the first-choice antibiotic was never prescribed. Conclusions: The under-prescription of amoxicillin highlights the low compliance with national and international guidelines on pharyngotonsillitis management. More must be done to improve rational use of antibiotics in the ED setting, and educational interventions are strongly needed. Disclosure(s): The study was partially funded by Lombardy Region (EPIFARM project). None of the authors has conflict of interest to disclose